Exploiting RAFT polymerization to tailor vehicles for uptake and release of polyphenols - Gomes, Catarina (2018)
Polyphenols have been attracting a growing interest by pharmaceutical, biomedical, cosmetic and food industries due to their proven beneficial effects on human health (e.g. antioxidant and anti-inflammatory effects with positive impact on protection of the cardiovascular system, cancer prevention or anti-aging actions). However, an effective bioavailability is an important practical issue. Failing to achieve it leads to no visible benefits of their use. Indeed, fast degradation in common conditions (owing to high sensitivity to temperature, pH and light), poor solubility in biological fluids and high metabolic and secretion rates are some well-known processes limiting polyphenols impact [1]. Thus, the development of vehicles aiming at stabilizing and protecting polyphenols from degradation, also allowing their sustained release, is a key issue to improve the effectiveness of such compounds. In this research, we explore RAFT polymerization to develop tailored materials useful as vehicles for the uptake and release of polyphenols. The preparation and testing of polymersomes based on RAFT-synthetized amphiphilic block copolymers and the generation of hybrid natural/synthetic materials, namely through the RAFT-mediated grafting of synthetic polymers on cellulose, are two different approaches here reported.